Bantuan Kemanusiaan Korban Bencana Alam Banjir Bandang dan Tanah Longsor di Masamba, Kabupaten Luwu Timur Sulawesi Selatan: Humanitarian Assistance for Victims of Natural Disasters Flash Floods and Landslides in Masamba, East Luwu Regency, South Sulawesi - Mustafa Mustafa; Fahmi Hafid; Nasrul Nasrul; Aminudin Aminudin; Amsal Amsal; Masudin Masudin; Sova Evie Sova Evie; Kadar Ramadhan; Hamsiah Hamsiah; Junaidi Junaidi; Zainul Zainul; Lisnawati Lisnawati; Putu Candriasih; Nurjaya Nurjaya; Elvyrah Faisal; Linda Linda; Lili Suryani; Sri M. Hasan; Hadriani Hadriani; I Wayan Supetran; Taqwin Taqwin; Andi Bungawati; Saharudin Saharudin; Hasanuddin Hasanuddin (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Monday, July 13th, 2020, Flash floods and landslides have hit the Masamba area, East Luwu Regency, South Sulawesi. The large number of victims and urgent needs and in order to ease the burden on the victims, the Academic Community of the Poltekkes Kemenkes Palu initiated a community service program in Masamba Regency. The purpose of this community service is to show the real action of the social care of the entire Civitas Poltekkes Kemenkes Palu to every disaster that occurs. The Humanitarian Aid Team of the Poltekkes Kemenkes Palu consists of 15 lecturers, staff and students of the Poltekkes Kemenkes palu. The method of implementing this service has four stages including planning to find funds, purchasing the needs of disaster victims, distributing assistance and the last stage, namely meeting the needs of victims. The aid was handed over by the Director of Poltekkes Kemenkes Palu, Palu through the Head of the Center for Research and Community Service to the Head of Disaster Prevention and Management Agency at the Emergency Response Command Post for Flash Floods and Landslides, North Luwu Regency, South Sulawesi Province on July 21, 2020 at the Central Disaster Management Command Post. Masamba Regency, East Luwu, South Sulawesi. The provision of Humanitarian Aid can be carried out properly. Communities victims of Flash floods as beneficiaries have received the assistance. It is recommended for this activity more team members so that the distribution of aid is wider and provides more opportunities for students to get directly involved in humanitarian activities